PERSPEKTIF WASIAT WAJIBAH TERHADAP ANAK TIRI (Kajian Persamaan Hak dengan Anak Angkat) - Hasan Basri, Amiruddin A. Wahab, A.Hamid Sarong. (Jurnal Ilmu Hukum, 2014)
Abstrak: It is mentioned in the Compilation of Islamic Law (Kumpulan Hukum Islam/ KHI), artcle 209 verse (1) stipulates that, the distribution of the property (inheritance) left by the adopted son is ruled in the articles 176 to 193. Meanwhile, for the foster parent who does not receive any wasiat, is entitled to the wasiat wajibah, 1/3 of the total property left by the adopted son. So does the adopted son, in verse (2) rules that for the step son, if he does not receive any wasiat, is entiteled to the wasiat wajibah, 1/3 of the total property left by the deceased foster parent. However, the case of the step son and parent are not coverd by any law. Thus, it is the purpose of this research to find and identify the law that could cover the status and right of the step son and parent in the family, or is legally accepted that theirs status is analogically equalized with the status of the adopted son and foster parent. This research is a prescriptive in nature, and used sebagai the yuridisempirist approach or fielf research. It found that, the living condition of the step child is legally equal to the adopted son, both are put under the custody of the step or foster parent. However, the step son and parent have no legal bindings, as that of the adopt son and foster parent on their right to the inheritance of either the step son or parent. They have been receiving benefit from the inheritance in the form of emdowment. The absenct of the law on this case, it is compulsaory to do ijtihad in the law of inheritance. It is advisable that the judge has to find and formulate the law (rechtsvinding dan rechtschepping), that cover the rights of those closed family who are not listed as the heirs, especially, the step son who lives with the step parent, that could be fallen under the law wasiat wajibah, because he could belong to the heir group dzawil arham. Keywords: Wasiat Wajibah and Step Son. Abstrak. Dalam KHI Pasal 209 ayat (1) disebutkan, harta peninggalan anak angkat dibagi berdasarkan Pasal 176 sampai dengan Pasal 193. Sedangkan terhadap orang tua angkat yang tidak menerima wasiat diberikan wasiat wajibah sebanyak-banyaknya 1/3 dari harta warisan anak angkatnya. Ayat (2) Terhadap anak angkat yang tidak menerima wasiat diberikan wasiat wajibah sebanyak-banyaknya 1/3 dari harta warisan orang tua angkatnya.Tujuan penelitian ini untuk mencari identifikasi hukum tentang kedudukan anak tiri dalam keluarga dapat dipersamakan dengan anak angkat. Jenis penelitian ini bersifat preskriptif sebagai dasar penerapan hukum terhadap hak anak tiri, dengan menggunakan metode penelitian yuridisnormatif atau disebut dengan penelitian dokmatif. Dewasa ini kehudupan anak tiri dalam keluarga sama dengan anak angkat. Anak tiri dari isteri dan dari suami menjadi tanggung jawab suami isteri. Namun secara hukum terhadap anak tiri belum ada aturan yang mengikat dalam hal perkara menerimaan hak dari orang tua tiri. Sehingga perlu dilakukan ijtihadterhadap persamalahan hak anak tiri, sebagai perkembangan hukum waris Islam. Disarankan kepada hakim untuk melakukan penemuan dan penciptaan hukum (rechtsvinding dan rechtschepping), terhadap hak-hak kerabat yang bukan ahli waris, terutama anak tiri yang hidup bersama dengan orang tua tirinya melalui wasiat wajibah, atau dapat digolongkan sebagai ahli waris dzawil arham. Kata Kunci: Wasiat Wajibah dan Anak Tiri.